2019
DOI: 10.1136/bcr-2019-231086
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-positive adult T-cell leukaemia/lymphoma with Epstein-Barr virus and hepatitis B coinfection

Abstract: Human T-cell lymphotropic virus (HTLV) is a human oncoretrovirus known to cause adult T-cell leukaemia/lymphoma (ATLL). Coinfection of human T-lymphotropic virus type 1 with Epstein-Barr virus (EBV) results in enhanced expression of the HTLV virus and leads to aggressive organ involvement from T-cell malignancy. It has also been observed that the prevalence of hepatitis B infection has been higher in patients with HTLV ATLL as compared with the general population in certain countries. We describe a case of a 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…EBV and HTLV-1 are both lymphotropic viruses, with EBV favoring B cells and HTLV-1 showing tropism towards T cells. While singular infections with either virus are often asymptomatic, there are a few instances of acute lymphoproliferative disease or progressive leukemia as the chronic infection progresses [35]. Genetic factors, notably HLA haplotype, have been associated with the development of both EBV-and HTLV-1-associated leukemia/lymphoma.…”
Section: Coinfectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…EBV and HTLV-1 are both lymphotropic viruses, with EBV favoring B cells and HTLV-1 showing tropism towards T cells. While singular infections with either virus are often asymptomatic, there are a few instances of acute lymphoproliferative disease or progressive leukemia as the chronic infection progresses [35]. Genetic factors, notably HLA haplotype, have been associated with the development of both EBV-and HTLV-1-associated leukemia/lymphoma.…”
Section: Coinfectionsmentioning
confidence: 99%
“…EBV antigens, EBNA-1 and LMP-1, are positive in ATLL cells associated with skin malignancies. Studies have also suggested that HTLV-1 infection enhances EBV spread into endothelial and epithelial cells [35,39]. ATLL carries a very poor prognosis due to chemoresistance and significant functional immunosuppression.…”
Section: Coinfectionsmentioning
confidence: 99%